Singing with the foodies (Orfeu, 2023)
In this work, the book “Cantando com as comilanças” is described and analysed, from the point of view of his contributions to field of literature on children´s musical-vocal development. Thus, the compositional characteristics, as well as its vocal technical objectives are identified in the thirteen vocal exercises, created by Juliana Melleiro. They are: expand children´s vocal range, explore facial resonators, develop different zones of textual articulation and enable vocal flexibility.